Optimization of oar blade design for improved performance in rowing - Caplan, N.; Gardner, T. N. (Journal of Sports Sciences, 2007)
The aim of the present study was to find a more optimal blade design for rowing performance than the Big Blade, which has been shown to be less than optimal for propulsion. As well as the Big Blade, a flat Big Blade, a flat rectangular blade, and a rectangular blade with the same curvature and projected area as the Big Blade were tested in a water flume to determine their fluid dynamic characteristics at the full range of angles at which the oar blade might present itself to the water. Similarities were observed between the flat Big Blade and rectangular blades. However, the curved rectangular blade generated significantly more lift in the angle range 0-90° than the curved Big Blade, although it was similar between 90 and 180°. This difference was attributed to the shape of the upper and lower edges of the blade and their influence on the fluid flow around the blade. Although the influence of oar blade design on boat speed was not investigated here, the significant increases in fluid force coefficients for the curved rectangular blade suggest that this new oar blade design could elicit a practically significant improvement in rowing performance.